A comparison of breeding bird populations inside and outside of European Badger Meles meles control areas. Issue 3 (2nd July 2020) - Kettel, Esther F.; Lakin, Ivan; Heydon, Matthew J.; Siriwardena, Gavin M.
ABSTRACT: Capsule: Analyses of survey data reveal no clear effects of the removal of European Badger Meles meles, a top predator in Great Britain, on bird populations. Aims: To investigate the effects of licensed Badger culling on bird populations in southwest England using ongoing monitoring data. Methods: Breeding Bird Survey data were used to compare population growth rates inside and outside Badger cull areas in southwest England over a five-year cull period (2013–2017), following a five-year baseline period (2008–2012). Comparative analyses of population growth rates of ground-nesters and of other species were tested for potential influences of Badger predation. We also compared species richness and diversity before and during culling, in treatment and control areas. Results: Most results were non-significant (48 of 58 species) but, where population growth rates were different ( P  < 0.1), they were higher for five species, and lower for seven, in cull areas. Ignoring significance, 33 population trends were more positive and 25 more negative within Badger cull areas. However, ground-nesting species, which were more likely to be sensitive to Badger predation, were not more responsive. Species richness declined significantly between pre-culling and culling periods in all areas, but diversity was unaffected and neither metric differed between treatment and control areas. Conclusion: There was no evidence for broad or consistent effects that support the existence of causal effects of Badger removal. Results for Skylark Alauda arvensis and Lapwing Vanellus vanellus suggested positive and negative effects of the cull, respectively, for these potentially sensitive species. Management and subtle habitat composition differences between study areas, and small sample sizes, may have limited statistical power, but there was no evidence that this affected inference. Monitoring and evaluation must continue as culling continues and is expanded, potentially increasing study power. Future research could also evaluate the potential ecological and demographic mechanisms behind any effects on birds of Badger removal.